2008
DOI: 10.1111/j.1537-2995.2008.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro properties of apheresis platelets during 7‐day storage after interrupting agitation for one or three periods

Abstract: Apheresis PLTs subjected to three periods without agitation maintained overall pH levels slightly greater than those of matched units subjected to one contiguous period without agitation. Other measures showed comparability of PLT in vitro variables with the two scenarios for interruption of agitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
1
29
1
Order By: Relevance
“…For example, PLTs activated by thrombin generate ROS, depolarize MMP, and induce MPTP by translocation of Bid and Bax proteins 25 . In addition, Trima‐collected PLTs undergoing a 30‐hour period without agitation are activated less than when the 30‐hour period was divided into three periods separated by a period of agitation 10 . Another study showed that PLTs that had undergone a prolonged period without agitation had properties that were not significantly different from those of agitated PLTs, provided that they were mixed once a day 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PLTs activated by thrombin generate ROS, depolarize MMP, and induce MPTP by translocation of Bid and Bax proteins 25 . In addition, Trima‐collected PLTs undergoing a 30‐hour period without agitation are activated less than when the 30‐hour period was divided into three periods separated by a period of agitation 10 . Another study showed that PLTs that had undergone a prolonged period without agitation had properties that were not significantly different from those of agitated PLTs, provided that they were mixed once a day 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggest that PLTs experience little motion during shipment 9 . Several studies have demonstrated that whole blood–derived and apheresis PLTs adequately maintain their in vitro properties with interruption of agitation (IA) periods of 24 hours or less 6,8‐12 . With IA periods of more than 24 hours, larger decrements in key PLT in vitro parameters, including PLT pH, morphology, extent of shape change, and hypotonic shock response, were observed 7,9,10 .…”
mentioning
confidence: 99%
“…PLT morphology was evaluated using phase microscopy as the percentage of discoid PLTs. Swirling that qualitatively assesses discoid PLTs was visually determined and scored with an arbitrary scale of 2 indicating good swirling, 1 indicating less than good swirling, and 0 when no swirling could be visually observed 9,10,12 …”
Section: Methodsmentioning
confidence: 99%
“…In a previous set of published studies, we have evaluated in vitro variables during storage of A‐PLTs stored in 100% plasma with scenarios in which agitation was interrupted under simulated shipping conditions 9‐12 . Our major conclusion was that the extent of in vitro changes after 5 days of storage was acceptable with 24 hours without agitation, whether the period without agitation was a continuous period (Day 2 to Day 3) or divided over 3 days 9,10 . In addition, delaying the placement of A‐PLT units on an agitator for 7 to 8 hours after the conclusion of the apheresis procedure did not have a detrimental influence on the retention of in vitro properties with a scenario that included a 24‐hour contiguous period without agitation 12 …”
mentioning
confidence: 99%
“…Many of these issues have been addressed in a number of well‐designed studies in laboratory as well as in real‐life settings 2‐10 . The results from such studies provide valuable general guidance for optimal handling of PCs during storage and transportation.…”
mentioning
confidence: 99%